ANALISIS FAKTOR-FAKTOR YANG MEMPENGARUHI KEPUASAN PENGGUNA SISTEM INFORMASI TERHADAP KINERJA INDIVIDU PADA PT. PLN (PERSERO) AREA MALANG - Achmad Erwinsyah Setyono; Rizka Fitriasari (Fakultas Ekonomi dan Bisnis Universitas Brawijaya, 2014)
The purposes of this research are to determine the effect of information system quality, information quality to user satisfaction, and user satisfaction to individual performance. Sample is taken by using purposive random sampling and data collection is using questionnaire to 65 employees at PT. PLN (PERSERO). This research is taken place at PT. PLN (PERSERO) AREA MALANG begin from April, 1 to April, 30 2015. Data analysis method is using Partial Least Square (PLS) approach which part of Structural Equation Model (SEM). Research result shown that information system quality and information quality have positive correlation to user satisfaction. System information quality variable is not significantly affects user satisfaction. While information quality is significantly affects user satisfaction. User satisfaction variable is significantly affects individual performance variable. Keywords : information system quality, information quality, user satisfaction, individual performance